The Benefits of Open Government Data Use: A Crosscountry Comparison - Mokobombang, N; Gutierrez, J; Petrova, K (Association for Information Systems (AIS), 2019)
Data produced by government have enormous importance; in addition to providing the information needed to run governance tasks related to internal processes, they can be used to create new sources of value by combining public datasets with private organisations’ data. In this regard, many countries have implemented Open Government Data (OGD) to unlock the potential value of public data. This study study is concerned with how government agencies create regulations about adopting OGD. The research examined five studies which investigated OGD programs in five different countries, and in one political and economic union. Drawing on the results of the analysis of the selected studies, it presents a list of categorised benefits based on OGD actors’ perspectives. Three categories of benefits are identified, namely 1) technical and operational, 2) economic, and 3) political and societal. This study gives a practical insight into how government agencies can use innovation to create, deliver and benefit from sustainable OGD value.
Keywords: Open Government Data; OGD; Dataset; OGD ecosystem; OGD benefits; User participation